Performance evaluation of shortest path routing algorithms in wide all-optical WDM networks - Zyane, Abdellah; Guennoun, Zouhair; Taous, Omar (2014 International Conference on Multimedia Computing and Systems (ICMCS), 2014)
This paper presents the effects of shortest path routing in wavelength-routed optical WDM networks; in particular we evaluated the effect of this routing scheme on the performance of wide all-optical WDM networks. Given a session request and a number of available wavelengths on each optical fiber, the routing and wavelength assignment (RWA) problem is to establish a lightpath (routing subproblem), i.e., to determine a path between two nodes, and also assign a wavelength along this path (wavelength assignment subproblem), so to maximize the number of satisfied requests for connections by taking into account some constraints. This study focuses on the routing subproblem in wavelength-routed all-optical WDM networks. We use Dijkstra's shortest path algorithm, to determine the shortest paths in terms of the number of hops (we assume that the links have the same weight, uniform traffic) from the source to other nodes in the network. We evaluate, for the first time, the performance of this algorithm for optical routing and we study the impact on the load distribution over the wide all-optical WDM network links. We also implement a simulation interface to evaluate this algorithm in wide all-optical WDM networks (different optical networks topologies were used in the simulation). This paper describes the inadequacy of the use of standard Dijkstra's shortest path routing, as it produces more unbalanced routes over the network links and unnecessary link overload.